Video as a tool for fostering productive discussions in mathematics professional development - Borko, Hilda; Jacobs, Jennifer; Eiteljorg, Eric; Pittman, Mary Ellen (Teaching and Teacher Education, 2008)
This article explores the use of classroom video as a tool for fostering productive discussions about teaching and learning. The setting for our research is a 2-year mathematics professional development program, based on the Problem-Solving Cycle model. This model relies on video from the teachers’ own classrooms and emphasizes creating a community in which members feel comfortable learning from video. We describe our experiences carrying out the Problem-Solving Cycle model, focusing on our use of video, our efforts to promote a supportive and analytical environment, and the ways in which teachers’ conversations around video developed over a 2-year period.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2006.11.012 2129771:A29SJWRW 2339240:HJGRG585 2405685:BWHR8RIX 5168324:KZZT3LBW
Keywords: C:United States; Mathematics education; Mathematics teachers; Professional development; Teacher learning; Video